Mechanical and optical properties of silk fabric/glass fiber mat composites: an artistic application of composites. Issue 8 (April 2018) - Yang, Yuqiu; Zhao, Defang; Xu, Jing; Dong, Yuying; Ma, Yan; Qin, Xiaohong; Fujiwara, Kiyoshi; Suzuki, Erika; Furukawa, Takashi; Takai, Yuka; Hamada, Hiroyuki
Currently, hybrid glass fiber-reinforced plastics (GFRPs) have attracted increasing attention as gradually common used materials. Glass/silk fiber hybrid reinforced plastic (GSFRP), a new kind of material, is designed aiming to create a kind of opaque effect of specific use. Three types of silk/glass composites with five layers of glass mats and a single layer of woven silk fabric lamina with small, medium and large crepe are fabricated by using the hand lay-up method to compare with pure GFRP. Optical properties, including the light transmission property and luminance distribution, were examined with regard to the specimens of GSFRP. Results indicate that light was diffused more efficiently by GSFRP than pure GFRP laminates. Moreover, the greater the crepe degree of silk fabric is, the more efficiently light is diffused and the rise of luminance suppressed. Furthermore, mechanical properties, including the flexural as well as the impact property, were examined through three-point bending and Izod tests, respectively. There is little negative influence on the flexural strength of GSFRP when silk inserted in layer 3 and, as the crepe degree of silk fabric increases, a slightly inferior effect on the impact test presented. From the scanning electron microscopy observation, it is found that the existence of silk fabric inserted in layer 3 could prevent further propagation of the crack and alleviate the delamination of the specimens during the bending process, improving resistance to delamination and bending.